2016
DOI: 10.1097/prs.0000000000002076
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Analysis of OnabotulinumtoxinA, AbobotulinumtoxinA, and IncobotulinumtoxinA: A Randomized, Double-Blind, Prospective Clinical Trial of Comparative Dynamic Strain Reduction

Abstract: Therapeutic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…We found that the dose ratio relationship between the two botulinum toxins was much more complex in the real world than was suggested by consensus panels [ 35 ] or meta-analyses of clinical trials [ 36 ], both of which concluded the botulinum toxins were equipotent and could be switched using a 1:1 conversion ratio. In this study, the incobotulinumtoxinA to onabotulinumtoxinA dose ratio was >1 across both conditions; there was considerable variability in the dose ratio and the inter-injection interval at an individual patient level, but mean dose ratios were all >1 and are consistent with the results of Kollowe and colleagues [ 18 ], Wilson [ 28 ], Thomas [ 29 ], and the preclinical studies cited above. Our results support that there is no fixed-dose ratio conversion between incobotulinumtoxinA and onabotulinumtoxinA, and consistent with the product label and recommendations from regulatory agencies, the potency units of onabotulinumtoxinA are not interchangeable with other botulinum toxin type A products [ 37 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that the dose ratio relationship between the two botulinum toxins was much more complex in the real world than was suggested by consensus panels [ 35 ] or meta-analyses of clinical trials [ 36 ], both of which concluded the botulinum toxins were equipotent and could be switched using a 1:1 conversion ratio. In this study, the incobotulinumtoxinA to onabotulinumtoxinA dose ratio was >1 across both conditions; there was considerable variability in the dose ratio and the inter-injection interval at an individual patient level, but mean dose ratios were all >1 and are consistent with the results of Kollowe and colleagues [ 18 ], Wilson [ 28 ], Thomas [ 29 ], and the preclinical studies cited above. Our results support that there is no fixed-dose ratio conversion between incobotulinumtoxinA and onabotulinumtoxinA, and consistent with the product label and recommendations from regulatory agencies, the potency units of onabotulinumtoxinA are not interchangeable with other botulinum toxin type A products [ 37 ].…”
Section: Discussionsupporting
confidence: 89%
“…With respect to its potential to treat blepharospasm, studies suggest that onabotulinumtoxinA (20 U) and abobotulinumtoxinA (60 U) significantly outperform incobotulinumtoxinA (20 U) based on dynamic strain reduction after injection into the glabella [ 28 ], and sustained improvements in facial synkinesias at week 4 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of incobotA (Merz Pharmaceuticals received FDA approval in 2010), there has been on-going debate within the literature as to the interchangeability of incobotA and onabotA at a uniform clinical dose conversion (1:1) ratio across a variety of indications (reviewed in [ 19 , 20 , 26 , 37 , 38 ]). Many studies refute the interchangeability of these products [ 24 , 25 , 39 , 40 , 41 , 42 ] and highlight that differences in injection volumes, patterns, and techniques, as well as distribution/diffusion patterns and other factors, vary between BoNT/A products [ 26 ]. For example, Moers-Carpi et al found that 20 U of onabotA was as effective as 30 U of incobotA at treating glabellar lines in a randomized, double-blind study [ 24 ], demonstrating the non-interchangeability of units of onabotA and incobotA in this indication.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Each of these neurotoxins is formulated differently, has a different manufacturing process, and demonstrates unique characteristics, and subsequently, these products are not interchangeable ( Table 2 ). 15 For safe clinical practice and achieving optimal results for a given indication, the practitioners need to understand the clinical issues of potency, conversion ratio, and safety (toxin spread and immunogenicity). A correct and optimal treatment plan and procedure requires an in-depth knowledge of the product(s) used, anatomy, and injection technique.…”
Section: Bont-a Formulationsmentioning
confidence: 99%